Penser le processus de remembrance à partir de la conception narrative de l’identité chez Paul Ricœur: le rôle des voix tierces et des ressources symboliques dans l’Ecriture ou la vie de Jorge Semprun - Katz-Gilbert, Muriel (B@belonline, 2021)
Tracing the traumatic past after a social disaster is not straightforward. This supposes a specific recollection process which mobilizes a narrative by definition polyphonic, in other words with several voices. Kaës advances the notion of ‘remembrance’ to qualify the fact of reconnecting between them pieces, shreds, scattered fragments of the memory tissue. But what are the narrative and more broadly discursive springs of such an operation? And what are the ethical and moral issues on the one hand but also at the identification level on the other? We will seek to identify the usefulness of a narrative conception of personal identity to shed light on these questions which we will address by analyzing in detail an extract from L’Ecriture ou la vie from Jorge Semprun. The story indeed gives a singular place to a song which, by the upheaval of the narcissistic contracts in which the author is caught, will momentarily create an unexpected breaking effect in the story.